Pelatihan Pembuatan Softener Pakaian dan Sabun Cuci Piring sebagai Alternatif Usaha dan Kegiatan Dharma Wanita Persatuan Kementerian Agama Kota Palangka Raya - Mukhlis Rohmadi; Nurul Septiana; Triwid Syafarotun Najah; Rahmah Alia (Pusat Riset dan Inovasi Nasional, 2023)
Dharma WanitaSatu (DWP) Ministry of Religion of Palangka Raya City decided to hold training on clothes softeners and dishwashing soap based on the current global economic conditions which have not yet stabilized after the pandemic that hit. The purpose of this training is to (1) provide skills to DWP members of the Ministry of Religion of Palangka Raya City in making clothes softener and dish washing soap, and (2) foster enthusiasm for DWP members. This activity is carried out in three stages. First, material about clothes softener and dish washing soap, as well as information about the tools and materials needed, as well as instructions for doing direct practice with the help of an instructor. Second, is the discussion and question and answer process regarding the training carried out. The hope of this activity is that the training participants will be able to practice the techniques for making dishwashing soap and clothes softener in their own homes. Apart from that, this activity can be used as a business opportunity to increase family income.